PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI TREBLE STORE SURABAYA - Saputra, Akhtar Alam; Dra.Yulyar Kartika.W.MM (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
ABSTRAK The study I found after analyzing the results of the influence of the Product Quality variable, Price Perception variable and Word of Mouth variable on Purchasing Decisions at Treble Store Surabaya. The method used is quantitative with a questionnaire as a tool for calculating data results, with analysis using IBM SPSS Version 27. The sample consists of 100 consumer respondents who shop online and offline at the Treble Store. This instrument test also involves validity and reliability tests. This analysis uses the results of multiple linear regression analysis tests, by analyzing the t test hypothesis, F test and coefficient of determination (R2). After the tests carried out, I found the t test results as follows: Product Quality has no influence on Purchasing Decisions, while Price Perception and Word of Mouth have a significant influence on Purchase Decisions at Treble Store Surabaya. Based on the results of the F test, the results I examined were the calculated F value of 98.586 > 2.699 with a significant value found as 0.00 < 0.05, then Ha will be accepted and Ho will be rejected. Thus, the results of the variables Product Quality (X1), Price Perception (X2) and Word of Mouth (X3) simultaneously have a significant influence on Purchasing Decisions (Y) at Treble Store Surabaya. Kata Kunci : Product Quality, Price Perception, Word Of Mouth, Purchasing Decisions